Moderní trendy v konstrukci kluzných ložisek turbodmychadel - Dobrovolný, Ondřej (Vysoké učení technické v Brně‎, Antonínská 548/1, 601 90 Brno, http://www.vutbr.cz/, 2014)
This bachelor thesis deals with the theme the modern trends in the design of bearings for turbochargers. The work is divided into three chapters. The first chapter describes the history, principles and construction of turbochargers. The second chapter attends to the theory of sliding bearings and their function. The third chapter deals with bearings used in turbochargers.
Keywords: kluzná ložiska; Turbocharger; journal bearing; kuličková ložiska; ball bearings; hydrodynamic lubrication; hydrodynamické mazání; Turbodmychadla